Nutritional value and consumer properties of bakery products with fructose for diabetic nutrition - Drobot, Vira; Shevchenko, Anastasiia (My University, 2017)
Nutritional value, consumer properties and freshness of bread with complex of additives was studied. These characteristics were determined by the organoleptic parameters by the expert estimation method, the structural and mechanical properties of the crumb on the automated penetrometer, the degree of freshness conservation by the indexes of lidding and moisture content, distribution and forms of moisture communication by differential thermal analysis on the derivatograph, the content of aromatic substances by the amount of bisulfite binding compounds.
Keywords: diabetes; freshness; bakery product; quality; fructose; кафедра технології хлібопекарських і кондитерських виробів